2011
DOI: 10.1039/c0sm00894j
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermodynamic aspects of the cylinder-to-sphere transition in amphiphilic diblock copolymer micelles

Abstract: The structure of diblock copolymers micelles depends on a delicate balance of thermodynamic forces driving the system towards equilibrium and kinetic factors which limit the systems' exploration of the phase space. The factors governing the morphological transition between cylindrical and spherical micelles are related to a fine balance between entropic forces from chains within the micellar core and corona. In order to understand and control these structures, it is important to gain insight into the fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 39 publications
6
71
0
Order By: Relevance
“…This is consistent with a systematic structural study where we found that the PEP1ÀPEO1 system shows a transition between cylinders and spheres at around 50% DMF mol fraction in the solvent mixture. 24 As it was extensively discussed there, this is a consequence of the balance of the elastic energy associated with the chain stretching inside the micellar cores and the steric/ elastic energy of the corona chains. While the former would favor cylindrical micelles since these exhibit the smallest radius for the same interfacial energy per chain,the corona free energy is higher in cylinders compared to spheres.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…This is consistent with a systematic structural study where we found that the PEP1ÀPEO1 system shows a transition between cylinders and spheres at around 50% DMF mol fraction in the solvent mixture. 24 As it was extensively discussed there, this is a consequence of the balance of the elastic energy associated with the chain stretching inside the micellar cores and the steric/ elastic energy of the corona chains. While the former would favor cylindrical micelles since these exhibit the smallest radius for the same interfacial energy per chain,the corona free energy is higher in cylinders compared to spheres.…”
Section: Resultsmentioning
confidence: 98%
“…As shown in a previous paper, 24 the system undergoes a thermally induced irreversible cylinder-to-sphere transition in a 51% DMF composition. We thus performed a TR-SANS experiment at D11, ILL on exactly the same micellar solution before and after heating the sample at 70°C for several hours.…”
Section: Tr-sans and Exchangementioning
confidence: 84%
See 2 more Smart Citations
“…The micelle diffusion coefficients were measured to be in the range of 2.3 – 3.2 × 10 −11 m 2 /s and the calculated hydrodynamic radii were in the range of 6.1 – 6.8 nm (Table 2) using the Stokes-Einstein relation (equation 1). We estimate the aggregation number of these micelles to be between 110 – 226, using the volume of a PEO-PCL diblock copolymer (and PEO and PCL densities of 1.125 and 1.14 g/mL, respectively), 3941 and assuming the micelle forms a sphere with hydrodynamic radius reported in Table 2 (this simplified calculation ignores many effects such as swelling of the micelle core with the co-solvent THF, swelling of the corona with water, the diffuse nature of the core-corona interface, and diffuse boundary between the corona and bulk solvent). Using this estimate of the aggregation number, we calculate the micelle concentration to be in the range of 5 – 9 × 10 18 micelles per L solvent, accounting for a critical micelle concentration of 0.002 wt%, reported previously for a PEO-PCL block copolymer in water.…”
Section: Resultsmentioning
confidence: 99%